(untitled) (International Scientific Journal Alfraganus, 2026)
The processes of deep changes, consistent reform and liberalization of all aspects of political and socio-economic life, democratic renewal and modernization of our society are developing rapidly in our country. In this regard, the huge tasks defined and consistently implemented in the way of forming a strong civil society are creating a solid foundation.